Hadith #38 - The Forty Hadith Qudsi - Abu Hurayrah (The Forty Hadith Qudsi)
On the authority of Abu Hurayrah (may Allah be pleased with him), who said that the Messenger of Allah (ﷺ) said: When Allah created Paradise and Hell-fire, He sent Gabriel to Paradise, saying: Look at it and at what I have prepared therein for its inhabitants. The Prophet (pbuh) said: So he came to it and looked at it and at what Allah had prepared therein for its inhabitants. The Prophet (pbuh) said: So he returned to Him and said: By your glory, no one hears of it without entering it. So He
Grade: Hasan